Circadian Disruptions Alter Consumption Timing and Exacerbate Binge-Like Eating in Mice - Christopher J. Mancuso; Samantha P. Bedard; Lindsay Gillikin; P. Evelyna Kambanis; Emily Schmitt; Kyle P. De Young (Journal of Circadian Rhythms)
Introduction: Circadian processes may be causal in the development and maintenance of binge eating. We used a rodent model of binge-like eating and a circadian disruption protocol to test whether circadian disruption causes increased consumption during 24h access to a high energy diet (HED). Method: Eight male mice underwent a two-week baseline with ad-lib standard chow and maintained a 12h light-dark schedule. Mice then completed two binge cycles. After, mice received a circadian disruption manipulation or remained on typical light schedule (i.e., were non-circadian disrupted). All mice received two binge cycles after manipulation. Chow and HED were measured every 12h and 24h. Independent samples t-tests compared consumption between the disrupted and non-disrupted groups. Results: Binge-like eating occurred in both experimental groups across all phases of the study. Circadian disrupted mice consumed more during HED access than non-disrupted mice, indicating that circadian disruptions may exacerbate binge-like eating. Circadian disruption also altered consumption timing; disrupted mice consumed more during typical rest hours (7:00–19:00) than non-disrupted mice but did not alter consumption during typical active hours (19:00–7:00). Conclusions: These results provide justiﬁcation for research examining circadian processes implicated in binge eating. Future research may inform on the utility of circadian regulating adjunctive treatment (e.g., bright light therapy or exercise).